Subtle perturbations of ovarian steroidogenesis in patients classified as Poseidon Group 3. Which consequences for therapeutic strategy? - Hugues, Jean Noel (Frontiers in Endocrinology, 2024)
The optimal strategy for stimulation of young women with a low ovarian reserve is still a challenging issue because the physio-pathogeny of this disorder is often unknown. As androgen production by the ovary plays a crucial role in folliculogenesis, it was tempting to speculate that subtle perturbations in ovarian steroidogenesis might participate to the low responsiveness to gonadotrophins. Indeed, in vitro analysis of human luteinized granulosa cells has recently provided evidence for some enzymatic deficits in steroidogenesis and altered response to gonadotrophins. Therefore, improving androgen environment of women classified in Poseidon Group 3 should be considered. In this clinical situation, the potential benefit of androgen supplementation or stimulation of theca cells by LH-activity products are respectively discussed.